ANALYSIS OF EMOTIONAL INTELLIGENCE AMONG MIDWIFERY AND NURSING STUDENTS IN THEIR CARE OF BPJS PATIENTS AT SALAKANAGARA UNIVERSITY IN 2025 - Galuh Chandra Dewi; Siti Maisaroh (Yayasan Education and Social Center, 2024)
The government's health insurance program called the National Social Security System (SJSN) began in January 2014. The Social Security Administration Agency as the implementing agency of the SJSN program in its efforts to support the overall participation of the National Health Insurance will improve the availability and quality of health facilities as well as the preparation of Service Operational Systems/Standards. The method used is descriptive analytical, with a cross sectional research design. The provision of health services to BPJS patients (dependent variables) is carried out at the same time as independent variable measurements to see the Emotional Intelligence of students, midwives, and nurses in providing services to BPJS patients. Data collection of both independent variables and dependent variables with a cross sectional approach was carried out together. The results of the study show that a person's emotional intelligence affects the provision of health services to BPJS patients. The contribution of this research lies in a comprehensive synthesis that provides a conceptual framework and practical recommendations for the development of policies, training, and service system innovations that are responsive to the needs and rights of patients This finding is expected to be an empirical foundation for the transformation of more inclusive and quality service practices and provide input to institutional leaders to be able to determine concrete steps in the implementation of education Midwifery and Nursing in improving the quality and skills of students, especially in improving the soft skills of graduates.